Exposure of men living in the greater Montreal area to organophosphate esters: Association with hormonal balance and semen quality. (August 2022) - Siddique, Shabana; Farhat, Imen; Kubwabo, Cariton; Chan, Peter; Goodyer, Cynthia G.; Robaire, Bernard; Chevrier, Jonathan; Hales, Barbara F.
Graphical abstract: Abstract: Exposure to organophosphate esters (OPEs) is extensive, yet few studies have investigated their association with hormone levels or semen quality. Here, we studied the association between urinary concentrations of OPEs and their metabolites with hormone levels and semen parameters in men (n = 117) predominantly in the 20–29 years age range who were recruited from the greater Montreal area between 2009 and 2012. Urine, serum, and semen samples were analyzed for OPEs, hormones, and semen quality, respectively. Bis(2-ethylhexyl) phosphate (BEHP), bis(2, 4-di- tert -butylphenyl) hydrogen phosphate (B2, 4DtBPP), tris(2-chloroisopropyl) phosphate (TCIPP), diphenyl phosphate (DPHP), bis (2-butoxyethyl) phosphate (BBOEP) and di-cresyl phosphate (DCPs) were detected in urine at a frequency ≥ 95%. The highest geometric mean concentration was observed for DPHP (18.54 ng/mL) and the second highest was B2, 4DtBPP (6.23 ng/mL). Associations between a doubling in analyte concentrations in urine and hormone levels and semen quality parameters were estimated using multivariable linear regression. B2, 4DtBPP levels were positively associated with total T3 (β = 0.09; 95% CI: 0.01, 0.17). DPHP was inversely associated with estradiol (β = -2.56; 95% CI: −5.00, −0.17), and TCIPP was inversely associated with testosterone (β = -0.78; 95% CI: −1.40, −0.17). Concentrations of BCIPP were inversely associated with sperm concentrations (β = -7.76; 95% CI: −14.40, −0.61), progressive motility (β = − 4.98; 95% CI: −8.71, −1.09), and the sperm motility index (β = -9.72; 95% CI: −17.71, −0.96). In contrast, urinary DPHP concentrations were positively associated with the sperm motility (β = 4.37; 95% CI: 0.76, 8.12) and fertility indices (β = 6.64; 95% CI: 1.96, 11.53). Thus, OPE detection rates were high and exposure to several OPEs was associated with altered hormone levels and semen parameters. The possibility that OPEs affect male reproduction warrants further investigation.